EFFECTIVENESS OF COMBINATION OF ETHANOL EXTRACT OF TURMERIC RHIZOME AND GREEN TEA LEAVES ON SERUM IRON LEVELS IN WISTAR RATS INDUCED WITH HEMOSIDEROSIS - Nasywa Nursyifa; henny juliastuti; Nurjannah Achmad (Universitas Aisyah Pringsewu, 2026)
This study aims to evaluate the effectiveness of the combination of ethanol extract of turmeric rhizome and green tea leaves on serum iron levels in Wistar rats induced hemosiderosis . This experimental study used 24 Wistar rats divided into four groups of six rats each, namely negative control, positive control, and two treatment groups with doses of 100 mg/kgBW and 200 mg/kgBW extract combination. Serum iron levels were measured after treatment, then analyzed using the Shapiro Wilk normality test, One Way ANOVA, and Tukey Post Hoc further test. The results showed that the positive control group had the highest serum iron levels , while the treatment group experienced a significant decrease in serum iron levels with a dose-response pattern; a dose of 200 mg/kgBW decreased iron levels more than a dose of 100 mg/kgBW. Statistical analysis showed significant differences between groups (p 0.05 ) , and the dose-response effect was confirmed by Tukey Post Hoc test. This decrease in serum iron levels is thought to be related to the activity of curcumin as an iron binder and antioxidant, as well as the catechin polyphenols in green tea, which work synergistically to reduce iron accumulation and oxidative stress. Based on these findings, it can be concluded that the combination of ethanol extract of turmeric rhizome and green tea leaves is effective in reducing serum iron levels in Wistar rats with induced hemosiderosis, thus having potential as an alternative or supportive therapy in controlling iron overload.